Performance- and safety-enhanced lentiviral vectors containing the human interferon-β scaffold attachment region and the chicken β-globin insulator - Ramezani, Ali; Hawley, Teresa S.; Hawley, Robert G. (Blood, 2003)
Retroviral vectors are the most efficient means of stable gene delivery to hematopoietic stem cells (HSCs). However, transgene expression from retroviral vectors is frequently subject to the negative influence of chromosomal sequences flanking the site of integration. Toward the development of autonomous transgene expression cassettes, we inserted the human interferon-β scaffold attachment region (IFN-SAR) and the chicken β-globin 5′ DNase I hypersensitive site 4 (5′HS4) insulator both separately and together into a series of self-inactivating (SIN) lentiviral vector backbones. Transduced cells of the human CD34+ hematopoietic progenitor line KG1a—pooled populations as well as individual clones harboring single integrants—were analyzed for reporter expression during culture periods of up to 4 months. Vectors carrying both the 5′HS4 insulator and the IFN-SAR consistently outperformed control vectors without inserts as well as vectors carrying either element alone. The performance of a set of vectors containing the murine stem cell virus long terminal repeat as an internal promoter was subsequently assessed during in vitro monocytic differentiation of transduced primary human CD34+ cord blood cells. Similar to what was observed in the KG1a hematopoietic progenitor cell model, optimal reporter expression in primary monocytes was obtained with the vector bearing both regulatory elements. These findings indicate that the 5′HS4/IFN-SAR combination is particularly effective at maintaining open chromatin domains permissive for high-level transgene expression at early and late stages of hematopoietic development, and thus could be of utility in HSC-directed retroviral vector–mediated gene transfer applications.